1984
DOI: 10.3109/03008208409013696
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycan Association with CollagendBand in Hyaline Articular Cartilage

Abstract: Proteoglycans of canine articular cartilage were labelled for transmission electron microscopy using the cationic copper phthalocyanin dye, cupromeronic blue, in a critical electrolyte concentration method. Much of the proteoglycan appeared to be structurally unrelated to collagen but a small proportion was positioned close to fibrils. On demonstrating the characteristic collagen banding pattern with uranyl acetate and phosphotungstic acid, it was evident that proteoglycan interacted with collagen at the d ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Evidence in favor of a strong interaction between these two matrix molecules comes from histological, biophysical, and biomechanical experiments. For example, electron microscopy studies, using cationic dyes (36) and immunoassay (37) techniques, have directly observed PG contact points on the collagen fibers. Further support for PG interacting with collagen came from in vitro biomechanical studies by Zhu et al (38).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in favor of a strong interaction between these two matrix molecules comes from histological, biophysical, and biomechanical experiments. For example, electron microscopy studies, using cationic dyes (36) and immunoassay (37) techniques, have directly observed PG contact points on the collagen fibers. Further support for PG interacting with collagen came from in vitro biomechanical studies by Zhu et al (38).…”
Section: Discussionmentioning
confidence: 99%
“…While the molecular components of the tissue have been well characterised and many of the collagen-collagen and collagen-proteoglycan interactions described under in vivo and in vitro conditions (Hendrix et al, 1982;Bayliss et al, 1983;Broom and Poole, 1983;Orford and Gardner, 1984;Müller-Glauser et al, 1986;Mendler et al, 1989;Furuto et al, 1991;Poole et al, 1992;Wu et al, 1992;Hagiwara et al, 1993;Hedbom and Heinegárd, 1993;Wotton and Duance, 1994;Weber et al, 1996;Danielson et al, 1997;Hagg et al, 1998), the three dimensional structure of AC is still controversial, due to the variation in preparation methods, imaging techniques and the variety of species in which AC has been studied.…”
Section: The Ultrastructure Of Mouse Articular Cartilage: Collagen Ormentioning
confidence: 99%
“…The main deformation that occurs in the deep zone is in the interterritorial matrix (IM), allowing the cellular columns to slide over and with respect to one another. the region of the tidemark, the weakest point of the cartilage (Fawns and Landells, 1953;Otterness et al, 1999).…”
Section: A Model Of Mouse Acmentioning
confidence: 99%
“…DISCUSSION Previous histochemical studies have indicated a close spatial relationship between proteoglycans and collagen in soft tissues, e.g. in tendon and annulus fibrosus (21) and in articular cartilage (22). Immunohistochemical examination has shown that the small dermatan sulfate proteoglycan decorin is associated with fibrils in tendon (23) and dermis (24), apparently because of interactions between the core protein and collagen.…”
Section: Figmentioning
confidence: 99%